(3GdZQjHf (B( (3ZQjH GdbQBf hGdMOjK (B)s - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg HHGH GdgeRI eY GdRGi (B: (3bhdg YR hLd McGjI (B: (3GTOO Hg CRQi , Ci bh Hg XgQi s
(3BNQgG (B:s
(3hBNQg eHJhQ CjVkG , jfJgi HGH GdTjf eY Gdfhf , Hbhdg (B: (3ai GdMOjK Cfg bGe ef Gddjd jUdi aMd TfGb GdbQHI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs